PEMBERDAYAAN FUNGSI KELUARGA (TELAAH TERHADAP TREN ANGKA KEKERASAN PADA ANAK) - Suryadi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2015)
Recently child violance phenomenon showed increasing trend figures. Particularly the numbers of child sexual abuse has been like a scary ghost. Indeed, some said that Indonesia has been categorized as emergency conditions sexual abuse in children. There are had appeared expression, Indonesia is a heaven for phedofil predators. This is due to legal sanctions have not been functioning as a deterrent effect. Child protection regulations have not been implemented yet maximally. In this situation, society has great expectations to law enforcement in order to take appropriate action. In addition, the institution of the family as a social institution is first and foremost for the child should be able to contribute to its function in order to reduce the number of child abuse. Families should be the frontline in the protection and fulfillment of children's rights. Further reinforced by the social networking community must participate in child protection which completed their growth process optimally.Key words : child violence, family function